2016
DOI: 10.1016/j.bbmt.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Detection of Anti–Human Leukocyte Antigen (HLA) Antibodies but not HLA-DP Loci Mismatches Can Predict Acute Graft-versus-Host Disease and Overall Survival in HLA 12/12–Matched Unrelated Donor Allogeneic Hematopoietic Stem Cell Transplantation for Hematological Malignancies

Abstract: The National Marrow Donor Program and Center for International Blood and Marrow Transplant Research provided guidelines for the use of anti-HLA antibodies and HLA-DP-mismatched loci in unrelated donor hematopoietic stem cell transplantation (HSCT). However, a deeper understanding of other potentially useful biomarkers for predicting clinical outcomes in HLA-A, -B, -C, -DRB1, -DQB1, and -DQA1 (12/12)-matched unrelated donor HSCT is needed to further improve clinical outcomes. We tested HLA genotyping for 123 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…In our secondary analysis, HLA alloimmunization was associated with acute GVHD, a finding that others have reported in unrelated donor HCT settings (Ansari et al , ; Pan et al , ). A question raised by this secondary analysis is why pre‐HCT HLA class I antibodies are associated with acute GVHD in our patients undergoing solely HLA‐matched HCT.…”
Section: Discussionsupporting
confidence: 71%
“…In our secondary analysis, HLA alloimmunization was associated with acute GVHD, a finding that others have reported in unrelated donor HCT settings (Ansari et al , ; Pan et al , ). A question raised by this secondary analysis is why pre‐HCT HLA class I antibodies are associated with acute GVHD in our patients undergoing solely HLA‐matched HCT.…”
Section: Discussionsupporting
confidence: 71%
“…Our results on the correlation of HLA antibodies with the severity of cGVHD are in accordance with a previously reported study [19]. Pan et al described a correlation between the presence in patients' serum of antibodies against HLA before or in the 1st month after transplantation and cGVHD.…”
Section: Discussionsupporting
confidence: 93%
“…They studied a cohort of patients diagnosed with hematological malignancies who received a BM/PBSCT with myeloablative conditioning. They found a higher rate of extensive cGVHD in the group with HLA antibodies in comparison to the group of patients without HLA antibodies prior to transplantation [19]. In our study, the HLA antibody status before transplantation was associated with the development of moderate to severe cGVHD.…”
Section: Discussionsupporting
confidence: 49%
“…Similarly, the results of Pan et al showed that the presence of anti-HLA antibodies and their dynamic changes after transplantation were associated with increased occurrence of grades II to IV acute and chronic GVHD, higher treatment-related mortality, and reduced OS and disease-free survival. 27 There was no significant difference in grades II-IV aGVHD, OS and disease free survival in patients receiving grafts from either HLA-DPB1 matched donors or HLA-DPB1 mismatched donors in this study. As we retrospectively examined our study group, we were not able to demonstrate the status of anti-HLA antibodies in our study group.…”
Section: Discussionmentioning
confidence: 48%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For instance, in the study by Loiseau et al reported increased frequency of severe aGVHD and poorer survival in two HLA-DP incompatibilities in a group of unrelated ASCT patients. 10 In this study they were not able show a significant relationship between HLA-DP mismatches and disease relapse.…”
Section: Discussionmentioning
confidence: 99%